Multi-Partite Structure of Demand-Supply Network Element - Fekete, I; Kallós, G; Hartványi, T (Acta Technica Jaurinensis, 2016)
In our recent article we investigate the utilization possibilities of usual time related, demand and supply data sets of an organization. We also create some others from those time related data sets, thanks to what we have the full set of links’ and nodes’ data for further analyses. We also evaluate some usual network analytical approaches to determine the characteristic structure of demand-supply network element (i.e. organization), the relevant network topology and sensitive to failure network skeleton.